ANALYSIS OF THE EFFECT OF FISHERMEN'S CHARACTERISTICS ON THE MANAGEMENT OF WEDGEFISH (Rhynchobatus sp.) AND GIANT GUITARFISH (Glaucostegus sp.) WITH PERCEPTION AS AN INTERVENING VARIABLE IN TASIKAGUNG FISHING PORT - Abdul Harits Ali Riza; Abdul Kohar Mudzakir; Hendrik Anggi Setyawan (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2022)
The endangered stingray species wedgefish (Rhynchobatus sp.) and giant guitarfish (Glaucostegus sp.) require good management, which must be implemented by examining the characteristics and perceptions of fishermen in Tasikagung Fishing Port, Rembang Regency. This study aims to know how the characteristics and perceptions of fishermen affected management support. The research method used in this study is a quantitative method and data analysis through linear regression and path analysis. Before being evaluated, the data were first validated with classical assumptions, including the multicollinearity test, linearity test, and normality test. The coefficient of determination (R2), the F test, and the t-test are then used to analyze the data to see whether the model is accurate. The sample determination method used causal-comparative, and the sampling method used was accidental sampling with 44 respondents. Fishermen characteristics as variable X (independent) are divided into 2 variables, namely Education (X1) and Knowledge (X2), Perception as variable Y (intervening), and Management Support as variable Z (dependent). Education and knowledge positively influence perception with a constant X1 = 0.177, and X2 = 0.556. Education, Knowledge, and Perception positively affect support with a constant X1 = 0.296; X2 of 0.028, and Y = 0.655. Y does not mediate the effect of X1 on Z, but does mediate the effect of X2 on Z.